Introduction: Hope over Time—Crisis, Immobility and Future-Making. Issue 4 (7th August 2016) - Kleist, Nauja; Jansen, Stef
ABSTRACT: This introduction discusses the hope boom in anthropological studies, suggesting that it reflects two converging developments: a sense of increasing unpredictability and crisis, and a sense of lack of political and ideological direction in this situation. We further identify two overall trends in the anthropological literature gathered under the rubric of hope: an emphasis on hopefulness against all odds and one on specific formations of hope and temporal reasoning.